Structural, chemical and optical characterizations of an experimental SiO2–Y-TZP ceramic produced by the uniaxial/isostatic pressing technique - Mosquim, Victor; Ferrairo, Brunna Mota; Vertuan, Mariele; Magdalena, Aroldo Geraldo [UNESP]; Fortulan, Carlos Alberto; Lisboa-Filho, Paulo Noronha [UNESP]; Cesar, Paulo Francisco; Bonfante, Estevam Augusto; Honório, Heitor Marques; Sanches Borges, Ana Flávia (Elsevier, 2020)
This study aimed to produce a new SiO2+Y-TZP ceramic via uniaxial/isostatic compression that was structurally and chemically characterized relating to its translucency and flexural strength. SiO2 and Y-TZP were mixed using a ball mill, pressed and sintered at 1150 °C. The optical and mechanical properties of the specimens were compared to lithium disilicate (LD) and zirconia-reinforced lithium silicate (ZLS) (Kruskal-Wallis, α = 0.05). The Fourier Transform Infrared Spectroscopy bands suggested an interaction between Si, O and Zr. Contrast ratio and translucency parameter of the experimental ceramic were higher and lower, (p = 0.000001) respectively, than those of the LD and ZLS. The experimental ceramic presented similar flexural strength to ZLS, but lower than LD (p < 0.0001). It can be concluded that this processing method is efficient to obtain a SiO2+Y-TZP ceramic and 1150 °C crystallizes SiO2 without inducing t-m transformation. The SiO2+Y-TZP ceramic presented lower translucency and higher masking ability than the commercially available glass-ceramics, but similar flexural strength to one glass-ceramics.
Keywords: Electron microscopy (B); SiO2 (D); X-ray methods (B)